Strategi Pemasaran Pt.Xyz Dalam Meningkatkan Penjualan Kabel Listrik - Wibowo, Wibowo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
With the growing trend of infrastructure in Indonesia like more high residence buildings, office buildings, and so on, the country needs more energy based on electricity. Within the trends of Indonesia Energy Outlook and statistics 2004 until 2013 the trends is growing fast pace that shows in the ratio, but some countryside of Indonesia was late to upgrade in infrastructure because the government much more concern in the Java-Bali and Madura based on the report, and the other details that said more province will need most electricity than Java. Energy and Human Resource Ministry have deployed 9 strategic initiatives, which one is build 35,000 Megawatt power plant. PT. XYZ as one of the electricity supplier in Indonesia which specialized in electricity cable of NYA, NYM, NYM-HY, NYY and NYAF. Based on growing trend of country infrastructure, we conducting a field research with source from PT. XYZ databased and supported with literature research that they are focusing in the electricity retailers, electricity store and contractors within every province starting with big cities like Medan, Pekanbaru, Jambi, Padang, Palembang, Bandar Lampung, Jakarta, Tangerang, Bandung, Serang, Bekasi, Bogor, Cikampek, Semarang, Solo, Surabaya, Denpasar, Mataram, Pontianak and Makassar and provide them with good quality product that has SNI brand on it. And implementing that within Marketing Mix (4P’s) that focuses on aluminium cable and audio cable.